An Analysis of the Racial Disparities Among Cervical Cancer Patients Treated at an Academic Medical Center in the Southeastern United States - Vengaloor Thomas, Toms (Cureus, 2021)
Objective The purpose of this study was to identify racial disparities in treatment outcomes, if any, among patients with carcinoma of the cervix treated at a tertiary care institution in the state of Mississippi. Methods A retrospective review of patients with carcinoma of the cervix treated in the Department of Radiation Oncology at our institution between 2010 and 2018 was performed. Data regarding demographics, disease stage, treatments administered, and follow-up were collected. Patient outcomes, including median survival and overall survival, were analyzed using the Kaplan-Meier method. All analyses were performed using SPSS Statistics version 24 (IBM, Armonk, NY). Results Between January 2010 and December 2018, a total of 165 patients with carcinoma of the cervix were treated at our institution. We had a significantly higher proportion of African American (AA) compared to Caucasian American (CA) patients (59.4 vs. 36.4%; p=0.03). There was a significant difference in the disease stage at the time of presentation between AA and CA in that compared to AA women, a higher number of CA patients presented with locally advanced disease [Federation of Gynecology and Obstetrics (FIGO) stages IB2 to IVA] (78.6 vs. 86.7%; p<0.001). However, a higher number of AA patients presented with metastatic disease at diagnosis compared to CA women (13.3 vs. 8.3%; p<0.001). Regarding their treatment, 157 (95.2%) underwent definitive chemoradiotherapy, while three (1.8%) had definitive surgery followed by adjuvant radiation or chemoradiation, depending on the risk factors identified operatively. The treatment details of five patients were not available. The median follow-up and the median survival of the entire cohort were 16 months and 79 months, respectively. In our cohort, there was no significant difference in overall survival between AA and CA patients at either three years (80 vs. 68%; p=0.883) or five years (77 vs. 68%; p=0.883). As expected, patients with locally advanced disease showed a significantly better median survival of 79 months compared to only 11 months for those with metastatic disease at their presentation (p<0.001). Conclusions Our study revealed that more AA women presented with metastatic disease compared to CA women. However, our analysis did not identify any racial disparities in the prognosis of the entire cohort.